ANALYSIS OF THE INFLUENCE OF MACROECONOMIC FACTORS AND THE INDONESIAN SHARIA STOCK INDEX (ISSI) ON THE NET ASSET VALUE (NAB) OF ISLAMIC MUTUAL FUNDS FOR THE PERIOD 2019-2023 - Risnawati; Misdiyono; Siti Aisyah (Asosiasi Dosen Muda Indonesia, 2026)
The development of Islamic mutual funds in Indonesia offers an attractive alternative for investors and has good potential for the economic sector in the future. However, throughout the period 2019 to 2023, the net asset value (NAV) of Islamic mutual funds experienced significant fluctuations, with a sharp decline in 2021 and 2022. This study aims to examine the influence of various macroeconomic factors as well as the Indonesia Sharia Stock Index (ISSI) on the net asset value (NAV) of Islamic mutual funds, both partially in the short and long term, as well as overall. The economic factors analyzed include inflation, exchange rate, BI rate and gross domestic product (GDP). A quantitative approach using secondary data was adopted in this study. The sampling technique applied is a saturated sample (census), while data analysis is carried out through the Vector Error Correction Model (VECM) model. The results revealed that in the short term, the exchange rate variable has a significant positive influence on the NAV of Islamic mutual funds. However, inflation, BI interest rate, GDP, and ISSI variables do not show a significant influence on NAV in the short term. Conversely, the long-term test results show that the exchange rate, BI interest rate, and GDP have a significant positive effect on the NAV of Islamic mutual funds, while inflation and ISSI do not have a significant effect. In addition, based on the results of the F test, inflation, exchange rates, BI interest rates, GDP, and ISSI variables simultaneously affect the net asset value (NAV) of Islamic mutual funds.